Psoriatic arthritis is associated with increased arterial stiffness in the absence of known cardiovascular risk factors: a case control study - Costa, Luisa; Caso, Francesco; D’Elia, Lanfranco; Atteno, Mariangela; Peluso, Rosario; Del Puente, Antonio; Strazzullo, Pasquale; Scarpa, Raffaele (Clinical rheumatology, 2012)
The objective of the study was the evaluation of arterial stiffness, a cardiovascular risk factor, in patients with psoriatic arthritis (PsA). Twenty PsA patients classified on the basis of the CASPAR criteria (M/W, 14/6; mean age, 38.6 years; range, 22–53), attending our out-patient clinic, and 20 healthy control subjects (M/W, 14/6; mean age, 38.7 years; range, 22–53) matched for age, weight, height and with similar cardiometabolic profile entered the study. An exclusion criterion was the presence of known cardiovascular risk factors. Central hemodynamic parameters and aortic pulse wave velocity (aPWV) were assessed non-invasively by a SphygmoCor device. A significantly higher aPWV was recorded in PsA patients when compared to controls. The difference remained statistically significant after adjustment for age, weight, height, heart rate (HR) and central mean pressure (mean±SE; PsA, 8.3 ± 0.2 versus control, 6.8 ± 0.2 m/s; p < 0.0001). Among PsA patients, aPWV was related to known duration of disease ( r = 0.63; p = 0.003). This result was confirmed after adjustment for the main confounders ( β = 0.011; p = 0.013). These results support the concept of psoriatic disease as a systemic condition involving not only the skin, joints and gastrointestinal tract but also arterial vessels. The involvement of the vascular system indicates the presence of pathogenetic mechanisms that could accelerate the atherosclerotic process in this condition.